2022
DOI: 10.3389/fpsyg.2022.865899
|View full text |Cite
|
Sign up to set email alerts
|

Nexus of Ethical Leadership, Career Satisfaction, Job Embeddedness, and Work Engagement in Hospitality Industry: A Sequential Mediation Assessment

Abstract: The paper proposes a research model explaining the sequential mediation effect of job embeddedness (JE) and work engagement (WENG) between ethical leadership (EL) and career satisfaction (CS). The model also examines whether JE heightens WENG, a factor indirectly influenced by ethical practices ending in employee satisfaction. The study used a time-lagged data collection procedure and survey responses of 247 hotel workers in China. Data were analyzed through structural equation modeling. The results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 86 publications
1
9
0
Order By: Relevance
“…The f-square value shows that ethical leadership positively affects work engagement (f-square = 0.221). The positive influence of ethical leadership on work engagement is supported by previous research (Ahmad & Gao, 2018;Khattak et al, 2022).…”
Section: Research Hypothesis Testingsupporting
confidence: 66%
See 1 more Smart Citation
“…The f-square value shows that ethical leadership positively affects work engagement (f-square = 0.221). The positive influence of ethical leadership on work engagement is supported by previous research (Ahmad & Gao, 2018;Khattak et al, 2022).…”
Section: Research Hypothesis Testingsupporting
confidence: 66%
“…Applying ethical leadership in banking organizations can form a work environment that encourages employees to be more attached to work (Ahmad & Gao, 2018). Leaders who implement ethical norms in the hospitality sector can increase work engagement in personal life and organizational practices (Khattak et al, 2022). Increased participation from employees will, in turn, increase work engagement, and then help to achieve or even exceed the targets.…”
Section: Discussionmentioning
confidence: 99%
“…Age, sex, marital status, tenure and direct manager's sex were included as control variables to reduce confounding issues (Pourhoseingholi et al, 2012). As the association between EL and JE has been established in previous research (Khattak et al, 2022), the impact of EL on JE was also controlled for when performing data analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In line with the JD-R model, job resources, personal resources and job demands remain the key antecedents of work engagement in the HTI. Recent hospitality and tourism studies have shown that green human resource management (Darban et al , 2022), management commitment to the ecological environment (Karatepe et al , 2022), fun in the workplace (Jyoti and Dimple, 2022), job crafting (Guo and Hou, 2022), informal learning (Rastogi and Karatepe, 2022), customer incivility (Ugwu et al , 2022), perceived innovativeness (Kim et al , 2022), servant leadership (Rabiul et al , 2022), inclusive leadership (Vakira et al , 2022) and ethical leadership (Khattak et al , 2022) have a significant impact on work engagement in the HTI. Meanwhile, green creativity and behaviours (Karatepe et al , 2022), work–family enrichment (Rastogi and Karatepe, 2022), innovative and extra-role behaviours (Ok and Lim, 2022) and adaptive behaviour (Kim et al , 2022) can be predicted by work engagement in the HTI.…”
Section: Literature Reviewmentioning
confidence: 99%